Spatio-temporal impacts of typhoon events on agriculture: Economic losses and flood control construction - Wei, Wei; Qian, Xiaoyan; Zheng, Qiongjie; Lin, Qing; Chou, Li-Chen; Chen, Xiding (Frontiers in Environmental Science, 2023)
Agricultural production has high correlations with natural disasters and water resource dynamic. Extreme rainfall brought by typhoons has a profound impact on agriculture in Taiwan. How typhoons impact agricultural activities and outputs is lacking research, especially in coastal regions such as Taiwan. In this report, the impacts of typhoon on agricultural loss from 2006 to 2019 in Taiwan was measured and explained the role of flood control construction in sustaining agricultural activities. With the help of Data Envelopment Analysis and geographical mapping, it is found that there are spatial differences in agricultural losses caused by typhoons. The main results indicate that the efficiency scores bring a inverse U-shape trend from the year 2007 (efficiency 0.718) to 2019 (efficiency 0.708). Looking further, Tainan City, Yunlin City, Chiayi County and other plain areas are vulnerable to disasters because the efficiency scores in these counties all below than 70%. It is found that the construction of flood storage and drainage facilities effectively slowed down the impact of rainfall brought by typhoon and promoted water storage functions.